2019
DOI: 10.1590/0034-7167/2018-0163
|View full text |Cite
|
Sign up to set email alerts
|

Educational hypermedia in nursing assistance at birth: building and validation of content and appearance

Abstract: Objective: to build an educational hypermedia about nursing care at usual risk birth and to perform validation of content and appearance. Method: methodological research carried out following the following stages: content and planning of modules; media production and organization of tutorial units; organization of student space, tutor and communication between them; availability of hypermedia; assessment by experts in nursing and informatics; and implementation of proposed suggestions. Results: educational h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
12

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 17 publications
0
14
0
12
Order By: Relevance
“…A hypermedia learning environment in mathematics" (Cueli et al, 2016), "Assistência de Enfermagem aos Períodos Clínicos do Parto: A hypermedia learning environment in nursing (Oliveira et al, 2019) "Alien Rescue: A hypermedia learning environment for science focus on astronomy and space travel (Pedersen & Liu, 2002) and "PHFSD: A pedagogical hypermedia environment for science focused on motion and force (Ajlouni & Jaradat, 2020). On the other hand, Del Río, Sanz, and Búcari (2019) demonstrate the positive impact of hypermedia material on students' mathematics learning, while the research of Liu (2005) found that hypermedia improved science-related knowledge among sixth-graders.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A hypermedia learning environment in mathematics" (Cueli et al, 2016), "Assistência de Enfermagem aos Períodos Clínicos do Parto: A hypermedia learning environment in nursing (Oliveira et al, 2019) "Alien Rescue: A hypermedia learning environment for science focus on astronomy and space travel (Pedersen & Liu, 2002) and "PHFSD: A pedagogical hypermedia environment for science focused on motion and force (Ajlouni & Jaradat, 2020). On the other hand, Del Río, Sanz, and Búcari (2019) demonstrate the positive impact of hypermedia material on students' mathematics learning, while the research of Liu (2005) found that hypermedia improved science-related knowledge among sixth-graders.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Integrated disciplines, active and student-centered methods have been a relevant challenge, instigating students and teachers to overcome the traditional method of teaching-learning (1)(2) . A study predicts that soon nurses will experience their practice permeated with technology, requiring curricular adaptation (3)(4)(5)(6) that favors the early use of media resources in the undergraduate course and in care, as in the case of mobile devices or applications (APPs) (7)(8)(9) .…”
Section: Introductionmentioning
confidence: 99%
“…Most of judges' suggestions were accepted aiming at adapting the Moodle course, such as text proofreading, adding content for a better understanding of specific themes and terminologies on the pillars of foot care management, as clarity of digital texts is an important aspect for meaningful learning (33) .…”
Section: Resultsmentioning
confidence: 99%
“…Studies of construction and validation of interventions and DL continuing education focus more in the context of hospital care (31)(32)(33) , indicating gaps in education aimed at primary care (31) . These, as well as the present, are structured in modules/thematic learning units, spaces for discussion, cases and didactic resources (27) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation